Methodical Assessment of River Periyar to Encounter Water Parameter Variation - V MurugaLal Jeyan, J; Rupesh, Akhila (International Journal of Engineering and Technology, 2018)
Water resource, being the most precious natural resource is getting depleted in the recent times in a drastic manner as ever before. The river water bodies, due to the discharge of industrial effluents and other wastes, is becoming more and more polluted, severely degrading its quality of usage. Recent studies have shown the serious need of Water quality assessment to know how far the resource is being polluted. The paper is on a survey work carried across the river Periyar at different sampling points to determine and analyzethe water pollution trends.